Diversity and abundance of terrestrial Gastropods on the slopes of Mount Arjuna-Welirang, East Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nurhayati PA, Affandi M, Nurinsiyah AS. 2021. Diversity and abundance of terrestrial Gastropods on the slopes of Mount Arjuna-Welirang, East Java, Indonesia. Biodiversitas 22: 4193-4202. Before this study, the latest list of land snail species from Mt. Arjuna-Welirang was published in 1952. The current study aims to update the list of terrestrial Gastropods in the area, focusing on Sumber Brantas Arboretum and Raden Soerjo Forest Park Conservation Area (Tahura), East Java, Indonesia. Live snails and dead shells were collected from 24 10 × 10 m2 sampling plots to determine species richness, composition, and abundance. Sampling was carried out by combining visual observation (direct collection) and sorting-sieving soil-leaf litter samples. Total 646 specimens belonging to eight families and 13 species were collected, all new records to the area. Thus, the number of species known from Mt. Arjuna-Welirang was increased to 16 species from nine families. The diversity index of the Mt. Arjuna-Welirang slope was 1.1, and the dominance index was 0.54. The Tahura had a higher diversity index than the Arboretum, at 2.0 and 0.38, respectively, but the dominance index for Tahura was lower (0.18 and 0.85, respectively). This was due to the dominance of Bradybaena similaris, an invasive species in the latter area. Less canopy cover and more human activity in the Arboretum are factors that might cause this discrepancy. Many land snail species are sensitive to desiccation and habitat disturbance. Therefore, minimizing habitat changes and human activities is necessary to maintain or increase native land snail species diversity.
Keywords: Arboretum of Sumber Brantas, Raden Soerjo Forest Park, Terrestrial Gastropods.